Emotional Content in Wikipedia Articles on Negative Man-Made and Nature-Made Events. (June 2018) - Greving, Hannah; Oeberst, Aileen; Kimmerle, Joachim; Cress, Ulrike
Wikipedia emphasizes the objectivity of content. Yet, Wikipedia articles also deal with negative events that potentially elicit intense emotions. Undesirable outcomes (e.g., earthquakes) are known to elicit sadness, while undesirable outcomes caused by others' actions (e.g., terrorist attacks) are known to elicit anger. Internet users' emotional responses are likely to end up in Wikipedia articles on those events as characteristics of Internet users spill over to Wikipedia articles. Therefore, we expected that Wikipedia articles on terrorist attacks contain more anger-related and less sadness-related content than articles on earthquakes. We analyzed newly created Wikipedia articles about the two events (Study 1) as well as more current versions of those Wikipedia articles after the events had already happened (Study 2). The results supported our expectations. Surprisingly, Wikipedia articles on those two events contained more emotional content than related Wikipedia talk pages (Study 3). We discuss the implications for Wikipedia and future research.